Study on Pile Bearing Capacity Improvement in Soft Soil After Vacuum Consolidation - Cindarto Lie; Wirawan, Adityaputera (Himpunan Ahli Teknik Tanah Indonesia, 2024)
The main problem in developing property over soft soil is significant settlement due to the consolidation process. The soil settlement, which will occur gradually throughout the years, will disrupt existing infrastructures, in this case bridges. To mitigate this issue, the common method is by speeding up the consolidation. The consolidation process must be sped up to avoid the differential settlement problem at the bridge abutments. Due to the limited supply of fill material, a vacuum consolidation method is adopted. In this method, a Prefabricated Vertical Drain (PVD) is installed, and a vacuum is applied to impose pressure as preloading. Because of the consolidation process, theoretically, the effective stress of the consolidated soil increases, and the soil shear strength does as well. Increasing the shear strength of the soils will increases the pile capacity. However, the interesting question is how much the shear strength of the soil can increase and impacts the pile capacity. In this paper, the shear strength improvement of the consolidated soil and the effect on pile bearing capacity is evaluated. This study used a series of in-situ tests that were carried out before and after the vacuum consolidation. A pile loading test using the Pile Dynamic Analyzer (PDA) method was carried out to verify the pile bearing capacity improvements. From the comparison result, it is shown that the theoretical capacity of the piles after consolidation were close to the pile test results.